(untitled) (Bangladesh Pharmaceutical Journal, 2023)
Numerous clinical and experimental studies have shown that individuals with a variety of orthopedic diseases can get benefit from the undenatured form of type II collagen (UC-II). It has proved its efficacy and long lasting effectiveness for several orthopedic patients throughout different countries in the world. But in Bangladesh it is not frequently prescribed yet. Therefore, we made the decision to conduct a survey-based study to determine the number of patients prescribed with UC-II under which pathological conditions and to what extent they have got relief from their joint associated ailments. To conduct the study, we visited the orthopedic department of various hospitals in Bangladesh and with consent from patients we collected pictures of prescriptions as well as got overview regarding their complications. We gathered photographs of 252 prescriptions from orthopedic department patients, among which only 31 patients were prescribed with UC-II. According to this study, 40.47 , 32.54 , 15.47 , 9.12 and 2.38 % of patients were over the age group of 60 , 50 , 40 , 30 and 20 - years respectively. We found that a range of individuals with various orthopedic problems such as osteoarthritis, spondylosis, right tibial plateau, paresthesia in right upper limb and various bone fractures were advised with UC-II. However, we discovered only in 12.30% of prescriptions that the doctors prescribed UC-II, indicating this is a less common practice in Bangladesh in spite of its huge potential to recover joint pain associated complications. Bangladesh Pharmaceutical Journal 26(2): 157-161, 2023 (July)